ANALISIS CHANGE ORDER RATIO PADA PROYEK KONSTRUKSI RUMAH TINGGAL STUDI KASUS DI DAERAH TANGERANG - Bataric, Rosani Surya; Sutandi, Arianti (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2025)
The construction industry plays an important role in economic growth, especially in infrastructure and housing. However, this industry is faced with various challenges, one of which is change orders that can hinder the smooth implementation of the project. Change order is a change in the provisions of the original contract document made in writing and documented between the project owner and the project implementer. These changes can have an impact on the price, project schedule, and schedule for contract payments. The purpose of this study is to analyze the magnitude of the change order ratio value and identify the causes of change orders based on job classification in a residential construction project. This research uses a case study of residential houses in the Tangerang area. Based on the results of research and calculation, the total value of change order ratio is 2.15%, for change order ratio in addition 1.60%, and change order ratio in subtraction 0.55%. Architectural and structural work which is the category of work with the largest change order impact on this residential construction project is one of the causes due to changes in the design of the building which causes changes in the volume of work. Abstrak Industri konstruksi memegang peranan penting dalam pertumbuhan ekonomi khususnya dalam bidang infrastruktur dan perumahan. Namun industri ini dihadapkan pada berbagai tantangan, salah satunya change order yang dapat menghambat kelancaran pelaksanaan proyek. Change order adalah perubahan ketentuan dokumen kontrak asli yang dibuat secara tertulis dan didokumentasikan antara pemilik proyek dan pelaksana proyek. Perubahan tersebut dapat berdampak pada harga, jadwal proyek, dan jadwal untuk pembayaran kontrak. Tujuan dari penelitian ini adalah untuk menganalisis besarnya nilai change order ratio dan mengidentifikasi penyebab terjadinya change order berdasarkan klasifikasi pekerjaan pada suatu proyek konstruksi rumah tinggal. Penelitian ini menggunakan studi kasus rumah tinggal di wilayah Tangerang. Berdasarkan hasil penelitian dan perhitungan, diperoleh nilai total change order ratio 2,15%, untuk change order ratio in addition 1,60%, dan change order ratio in subtraction 0,55%. Pekerjaan Arsitektur dan Struktur yang menjadi kategori pekerjaan dengan dampak change order terbesar pada proyek konstruksi rumah tinggal ini salah satu penyebabnya adalah karena adanya perubahan pada design bagunan yang menyebabkan adanya perubahan pada volume pekerjaan.